(untitled) (Journal of Medical & Health Sciences Review, 2025)
This study evaluated the growth performance, hematology, and serum biochemistry of Genetically Improved Farmed Tilapia (GIFT, Oreochromis niloticus) reared in cage culture using two commercial feeds, Hi-Tech (pelleted) and Supreme Aqua (granular). Floating cages were installed at Piala Lake, Dera Ghazi Khan, Pakistan, and stocked with acclimatized fingerlings. Physicochemical water parameters were monitored weekly, and fish were fed at 5% body weight. Blood samples were collected for hematological and biochemical analyses. Results showed that fish fed with Supreme Aqua feed exhibited higher average weight gain (61.66 ± 3.53 g), biomass (440 ± 7.62 kg), and lower feed conversion ratio (1.82 ± 3.73) compared to Hi-Tech feed. Mortality was also lower in the Supreme Aqua group. Hematological parameters (Hb, RBC, WBC, PLT, HCT, MCV, MCH, MCHC) showed no significant differences between treatments. Serum biochemistry indicated significantly higher alkaline phosphatase and creatinine levels in Hi-Tech fed groups, while ALT and AST remained comparable. Seasonal analysis revealed progressive weight gain from May to October, strongly correlated with temperature variations. Overall, Supreme Aqua feed demonstrated better growth efficiency in cage culture systems. The findings suggest that granular feeds may enhance productivity and profitability in tilapia aquaculture.